Signless Laplacian energy of interval-valued fuzzy graph and its applications - Romdhini, Mamika Ujianita; Al-Sharqi, Faisal; Nawawi, Athirah; Al-Quran, Ashraf; Rashmanlou, Hossein (Penerbit Universiti Kebangsaan Malaysia, 2023)
An interval-valued fuzzy graph (IVFG) emanates from a fuzzy graph (FG) where the membership is given in interval form. This framework give the user more flexibility in dealing with fuzzy information. In this paper, the signless Laplacian matrix of an interval-valued fuzzy-directed graph is defined. The eigenvalue, spectrum, spectral radius, and energy of an interval-valued fuzzy-directed graph associated with the signless Laplacian matrix are reported. In addition, the lower bound of the signless Laplacian energy in this graph is highlighted. Finally, these tools are employed to build an algorithm that helps in solving some real live problems.